1980
DOI: 10.1056/nejm198003203021201
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Retinopathy in Diabetics with Elevated Blood Pressure

Abstract: The incidence of retinopathy was assessed in 188 diabetic and 284 nondiabetic Pima Indian adults six years after an initial examination had shown each to be free of retinopathy. Exminations included direct ophthalmoscopy through dilated pupils. The incidence of retinal lesions was strongly related to the presence of diabetes and, among the diabetic subjects, to insulin treatment, disease duration, plasma glucose concentration, and presence of other complications such as proteinuria, loss of deep tendon reflexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
114
3
3

Year Published

1986
1986
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 368 publications
(131 citation statements)
references
References 8 publications
11
114
3
3
Order By: Relevance
“…Systolic blood pressure, associated with baseline retinopathy [28,34] and retinopathy progression [6], was also a powerful independent predictor of SVI. The relation between arterial pressure, retinopathy and the potential for visual impairment has been noted in many other studies [22,31,35,36]. Most recently, tight control of raised blood pressure in Type II diabetes has been shown to slow the progression of retinopathy and reduce the need for photocoagulation compared with less tight pressure control [41].…”
Section: Discussionmentioning
confidence: 91%
“…Systolic blood pressure, associated with baseline retinopathy [28,34] and retinopathy progression [6], was also a powerful independent predictor of SVI. The relation between arterial pressure, retinopathy and the potential for visual impairment has been noted in many other studies [22,31,35,36]. Most recently, tight control of raised blood pressure in Type II diabetes has been shown to slow the progression of retinopathy and reduce the need for photocoagulation compared with less tight pressure control [41].…”
Section: Discussionmentioning
confidence: 91%
“…Grading was based on the fundoscopic findings of the worst eye at each exam. The "none" group included eyes with hard exudates only, as previously they have been shown to be common in Pima Indians without diabetes [11]. The "non-proliferative" group comprised those with at least a single microaneurysm in one eye but no signs of proliferative retinopathy.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence in this study is somewhat lower (25.5%). Reported incidence rates for diabetic retinopathy vary; the UK Prospective Diabetes Study (UKPDS) reported a 6-year cumulative incidence of 22% (3), whereas the WESDR study reported a 34 -47% 4-year cumulative incidence (36). Among the Pima Indians, we previously reported a 4-year cumulative incidence of 16.8% (38).…”
Section: Diabetes Vol 56 April 2007mentioning
confidence: 99%